2005
DOI: 10.1167/iovs.05-0410
|View full text |Cite
|
Sign up to set email alerts
|

BacillusEndophthalmitis: Roles of Bacterial Toxins and Motility during Infection

Abstract: The results demonstrate that, in addition to quorum-sensing-controlled toxin production, bacterial migration within the eye contributed to the rapidly fulminant and destructive course of Bacillus endophthalmitis. Motility and quorum-sensing may therefore represent possible targets for the development of therapies designed to attenuate the devastating effects of Bacillus in the eye during endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
72
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…In this study, virulence was strongly decreased by both forcefeeding and intrahemocoelic injection. This is the first demonstration of the role of FlhA in the virulence of B. thuringiensis in insects, but a recent study showed an effect on rabbit endophthalmitis (10). Moreover, so far, no other B. thuringiensis factors have been described to play a role by both oral and intrahemocoel inoculation.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, virulence was strongly decreased by both forcefeeding and intrahemocoelic injection. This is the first demonstration of the role of FlhA in the virulence of B. thuringiensis in insects, but a recent study showed an effect on rabbit endophthalmitis (10). Moreover, so far, no other B. thuringiensis factors have been described to play a role by both oral and intrahemocoel inoculation.…”
Section: Discussionmentioning
confidence: 76%
“…However, it should also be taken into consideration that B. cereus is able to produce additional food spoilage and virulence factors, including phospholipases, proteases, hemolysins, and enterotoxins, which are unambiguously of medical and economical impact (10,35,54). lux gene reporter systems, similar to the one described in this work, might also be useful for monitoring enterotoxin expression and could add important information to the hazard identification of different food systems.…”
Section: Discussionmentioning
confidence: 99%
“…6 For instance, bacterial communication through motion is believed to be an important factor for infections and for bacterial resistance to antibiotics. 7,8,37 Consequently, the development of sensitive force and motion probes, 9 which can match the time and length scales of microorganisms, has been an important element in the study of motile microorganisms.…”
mentioning
confidence: 99%